INTEGRASI FITUR BACK-END UNTUK PENGEMBANGAN SISTEM INFORMASI E-ABSENSI KEHADIRAN MAHASISWA BERBASIS FRAMEWORK CODEIGNITER - Oman somantri; Dyah Apriliani (UNIVERSITAS STEKOM, 2020)
The presence of students in the classroom is one way to supervise students. Evidence of the presence of students in the classroom is still done manually, ie signature presence. The aim of this research is to build a back-end information system that can be used to manage student attendance recapitulation named e-abseni. The Codeigniter framework is used to build this system in order to get a good result. Benefits of the research conducted is to provide assistance in policy making about the presence of students. With e-absensi is expected to assist in the process of calculating the attendance of students in the class that the number of attendance is a requirement to take the exam, both Mid Semester Exam (UTS) and Semester Exam (UAS).